Canine skin and conjunctival swab samples for the detection and quantification of Leishmania infantum DNA in an endemic urban area in Brazil. - Sidney de Almeida Ferreira; Rodrigo Souza Leite; Leonardo Trindade Ituassu; Gregório Guilherme Almeida; Daniel Menezes Souza; Ricardo Toshio Fujiwara; Antero Silva Ribeiro de Andrade; Maria Norma Melo (Public Library of Science (PLoS), 2012)
Background We evaluated kDNA PCR/hybridization and quantitative real-time PCR (qPCR) targeting the gene of DNA polymerase of Leishmania infantum for CVL diagnosis and assessment of parasite load in clinical samples obtained invasively and non-invasively. Methodology/principal findings Eighty naturally infected dogs from an endemic urban area in Brazil were used. Animals were divided into two groups based on the presence or absence of CVL clinical sings. Skin biopsies, bone marrow, blood and conjunctival swabs samples were collected and submitted to L. infantum DNA detection. In addition, anti-Leishmania antibody titers were measured by Immunofluorescence antibody test. The symptomatic dogs had increased titers compared to asymptomatic dogs (P = 0.025). The frequencies of positive results obtained by kDNA PCR/hybridization for asymptomatic and symptomatic dogs, respectively, were as follows: right conjunctiva, 77.5% and 95.0%; left conjunctiva, 75.0% and 87.5%; skin, 45.0% and 75.0%; bone marrow, 50.0% and 77.5%; and blood, 27.5% and 22.5%. In both groups, the parasite load in the skin samples was the highest (P<0.0001). The parasite loads in the conjunctival swab and bone marrow samples were statistically equivalent within each group. The parasite burden in conjunctival swabs was higher in the dogs with clinical signs than in asymptomatic dogs (P = 0.028). This same relationship was also observed in the bone marrow samples (P = 0.002). No differences in amastigotes load in the skin were detected between the groups. Conclusions The conjunctival swab is a suitable clinical sample for qualitative molecular diagnosis of CVL. The highest parasite burdens were detected in skin regardless of the presence of VL-associated clinical signs. The qPCR results emphasized the role of dogs, particularly asymptomatic dogs, as reservoirs for CVL because of the high cutaneous parasite loads. These results may help to explain the maintenance of high transmission rates and numbers of CVL cases in endemic urban regions.